2020
DOI: 10.2478/atd-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Based Learning Module for Critical Thinking Ability in Elementary School: Systematic Search

Abstract: Introduction:The purpose of this article is to examine the use of socio-cultural based learning modules for developing critical thinking skills in elementary school children.Methods:This article is a systematic review that collects data from relevant indexed journals.Results:The findings are discussed in theoretical studies so as to produce conclusions. Well-structured socio-cultural modules can provide many benefits for students, namely for students who are actively involved in learning activities, and they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…LSA results show that the appropriation of cultural-based teaching still faces several challenges within the remedial education context. Challenges identified in this study, such as teaching resources, existing curriculum, teacher knowledge, and time allocation, are not unique to Malaysia and exist in numerous other developing nations (Amalia & Wuryandani, 2020). Other than that, the problems established are significant to consider when making a plan for teaching with cultural elements, especially in the context of remedial education in Malaysia.…”
Section: Discussionmentioning
confidence: 92%
“…LSA results show that the appropriation of cultural-based teaching still faces several challenges within the remedial education context. Challenges identified in this study, such as teaching resources, existing curriculum, teacher knowledge, and time allocation, are not unique to Malaysia and exist in numerous other developing nations (Amalia & Wuryandani, 2020). Other than that, the problems established are significant to consider when making a plan for teaching with cultural elements, especially in the context of remedial education in Malaysia.…”
Section: Discussionmentioning
confidence: 92%
“…Concurrently, teachers encountered challenges in the curriculum structure of remedial education and expressed concern regarding the lack of emphasis on cultural-based learning. [44] reported that the teaching strategies introduced in the subject curriculum structure become challenging during the transition to classroom learning when more teacher creativity would be required to process teaching materials. Students' cultural background diversity awareness should also be incorporated into the curriculum [45].…”
Section: Discussion 421 Contemporary Pedagogical Circumstancesmentioning
confidence: 99%
“…But, unfortunately almost there is no teaching and learning material or educational media that use pantun on contextual in school circles. Education based on cultural literacy can guide students to know their culture and building student's character too (Amalia & Wuryandani, 2020;Naderer, 2021).…”
Section: Discussionmentioning
confidence: 99%